ORGANIZATION OF UPPER-FORMERS EDUCATION OF «INFORMATICS» IN THE PHYSICAL AND MATHEMATICAL PROFILE CLASSES - Anna L. Fedorchuk (Information technologies and learning tools, 2014)
The article reviews the main theoretical and methodological problems of organization the learning, development priorities of upper-formers to subject "Informatics" in physical and mathematical profile classes. It is analyzed the content and organization of training course «Informatics» for upper form pupils. There are highlighted the goals, objectives, requirements, functions, principles, methodological approaches, methods, forms and means of training; specificity of the organization of learning the subject «Informatics» of pupils in classes of physical and mathematical profile. It is defined approach to the organization of profile study of computer science and computer technology that will directly affect the general education of students and their further professional development.